Characterization of protein secondary structure. - Ganapathiraju, M.K (IEEE Signal processing magazine)
What do proteins look like? Proteins are composed of fundamental building blocks of chemical molecules called amino acids. When a protein is synthesized by the cells, initially it is just a string of amino acids. This string arranges itself in a process called protein folding into a complex three-dimensional structure capable of exerting the function of the specific protein. We briefly review the fundamental building blocks of proteins, their primary and secondary structure.